Comportamento de um grupo isolado de muriqui-do-norte (Brachyteles hypoxanthus) no Espírito Santo - Silva, Barbara de Almeida (2008)
Several studies have shown the effects of habitat size and quality and demographic factors on intraspecific behavioral differences in primates. In the last 25 years, studies of the northern muriqui (Brachyteles hypoxanthus) at the Private Nature Reserve Feliciano Miguel Abdala, Caratinga, Minas Gerais, have provided insights into their behavior. However, it is not known whether the behavior of other northern muriqui populations living under different demographic and environment conditions is similar to that of the Caratinga muriquis. This study was conducted on one muriqui group of 13 to 15 individuals that inhabits a 128 hectare fragment of secondary vegetation at Saint Maria de Jetibá (SMJ). The aim of this work is to characterize the northern muriqui’s behavior at SMJ and to compare their behavior patterns with those of other northern muriqui populations. The focal animal method of behavioral sampling was used to collected data systematically, and all rare events observed were recorded opportunistically. Approximately 185 hours of focal animal samples were collected.Results suggest that the size and the composition of the group may affect some aspects of the muriqui’s social behavior. Specifically, the lower number of adult males affects their affiliative interactions, expressed primarily by the low frequency of embraces between adult males in the SMJ group, but does not seem to affect the proximity between adult males, which is similar across groups